Angelology - Trussoni, Danielle (New York : Viking, 2010)
When twenty-three-year-old Sister Evangeline accidentally stumbles upon some mysterious letters exchanged between the late mother superior of her convent and the famous philanthropist Abigail Rockefeller, she is thrust into an ancient conflict between the Society of Angelologists and the monstrously beautiful descendants of angels and humans, the Nephilim.
Keywords: Nuns -- Fiction; Angels -- Fiction; Armageddon -- Fiction; Suspense fiction; Fantasy fiction